2021
DOI: 10.9734/ajacr/2021/v9i330216
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potentials of Cynodon dactylon on Heavy Metal Contaminated Soils from Challawa Industrial Estate, Kano-Nigeria

Abstract: This study investigated the phytoremediation potentials of Cynodon dactylon in heavy metal contaminated soils of Challawa Industrial Estate, Kano, Kano State, Nigeria. A total of 100 samples comprising of 50 soils and 50 plant parts of C. dactylon were evaluated for the presence of heavy metals by the use of atomic absorption spectrophotometry (AAS) method. Extent of heavy metal soil contamination and phytoremediation potentials of the study plant were assessed by the use of metal contamination factor (Cf) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…The contaminated soils of this study negatively influenced the development of Bermuda grass, and this is in accordance with previous reports (e.g., [ 18 , 28 , 29 ]). Nevertheless, the fact that the biomass was the only parameter to significantly decrease under contamination points to the tolerance of this grass to PTMs in the soil and reinforces its recommendation for rehabilitation and phytostabilization of contaminated areas [ 30 , 31 , 32 ]. The development of the African daisy was also compromised in the contaminated soils, especially in the gold tailings, where all seedlings died before full development of the first leaves, in the treatment with A. castanea .…”
Section: Discussionmentioning
confidence: 91%
“…The contaminated soils of this study negatively influenced the development of Bermuda grass, and this is in accordance with previous reports (e.g., [ 18 , 28 , 29 ]). Nevertheless, the fact that the biomass was the only parameter to significantly decrease under contamination points to the tolerance of this grass to PTMs in the soil and reinforces its recommendation for rehabilitation and phytostabilization of contaminated areas [ 30 , 31 , 32 ]. The development of the African daisy was also compromised in the contaminated soils, especially in the gold tailings, where all seedlings died before full development of the first leaves, in the treatment with A. castanea .…”
Section: Discussionmentioning
confidence: 91%
“…The results also showed that the plant roots have absorbed more HM concentration than the shoots, as the current study results. Shuaibu et al [51] observed the phytoremediation potentials of C. dactylon on HM polluted soils from Challawa Industrial Estate, Nigeria. They found that the concentration of the metals in the C. dactylon from control and polluted sites were noted to be in the order of Cu (33.60 mg/kg) > Mn (12.67 mg/kg) and Cu (138.35 mg/kg) > Mn (28.40 mg/kg), respectively.…”
Section: Bioconcentration (Bcf %) and Translocation Factor (Tf %) Of ...mentioning
confidence: 99%
“…Investigaciones científicas previas han demostrado el potencial de fitorremediación de la especie C. dactylon al acumular metales pesados de sitios contaminados mediante fitoextracción y fitoestabilización (p.e. (Mishra et al, 2020;Sampanpanish et al, 2006;Shuaibu et al, 2021)). En cuanto a la especie P. afra, la evaluación de su capacidad de fitorremediación de Cr(VI) representa una gran aportación en el alcance de la aplicación de este tratamiento biológico complementando el catálogo de especies utilizadas para estos fines y en la comprensión de las interacciones en el sistema suelo-planta-contaminante que involucra a esta especie vegetal.…”
Section: Introductionunclassified
“…Respecto a la especie S. trifasciata, se observó una eficiencia similar con un valor de 81.96%, FBC de 0.738 y FT de 0.008. La concentración del contaminante en el suelo para ambos casos se reportó inferior a los límites máximos permisibles establecidos por la normatividad mexicana para suelos agrícolas, comerciales o residenciales.En cuanto a las inverstigaciones internacionales,Shuaibu et al, (2021) estudiaron el potencial de fitorremediación del pasto C. dactylon en suelos que presentaron una alta contaminación con Cd, considerablemente con Cu y Cr, y moderadamente con Fe, Mn, Zn, Ni y Pb. Después del tratamiento biológico, se obtuvieron valores de FBC>1 y FT<1 para Cd, Cr, Cu, Mn, Ni, Pb y Zn, así como FBC>1 y FT<1 para Fe, lo cual es un indicador de que la planta es capaz de acumular estos metales pesados en las raíces, así como de extraer Fe, volviéndola útil tanto para procesos de fitoestabilización y fitoextracción en suelos multimetálicos contaminados.…”
unclassified